Strategi Pembelajaran dalam Perspektif Islam - Junaidah, Junaidah (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2015)
National education  in the  face of  crisis,  relating to quality relevance and effefficiency ofexternallitisme,  and  management.  A  further  proposed  at  least  the  issue    of    national education   systems:    (1)    behavior   morale    students,    (2)    the  distribution  of  the  study ,  (3)  arestill  education  sy stem  internal,  lack  of  efficiency (4)  the  organizational,  (  5  )  the  management  ofeducation  is  not  consistent  with  the  development  of  a  national  (6)  Resources  not  professional. One  side  weakness  who  handled  Abudin  Nata  is  concerned  by  the  lack  of  a  strategy  for learning,  but  the strategy of hold important roles in the success learning process.The purpose  this  is  journal  ia  lesson  in  Islam  he thought  Abuddin  Nata perspective.  Result of search  for  a  literature  indicate  a  lesson  in  islam's  perspective  is  its  base  in  the  preliminary framework  changes  expected  to  be  on  the  educational  objectives  on  the  establishment  of  such behavior  in  a student. The  approach  in learning  is  part  of  a  strategy of  learning  that  this  approachusing  a  yardstick  a science  discipline  objectives  to  be  achieved,  measures  to  be  used,  or  mark used, this  approach  with  regard  to  the  teaching  and  learning  is  most  properly  and  effectivel y to achieve  the  target.In  the  implementation  of  the  acquisition  may  be  conducted  through  the  model of  islamic  education  oriented  to  approach  cbsa  skills  and  learning  process,  quantum  teaching, problem solving and the  formation of memories.